Synchrosqueezed wavelet transform for damping identification. (1st December 2016) - Mihalec, Marko; Slavič, Janko; Boltežar, Miha
Abstract: Synchrosqueezing is a procedure for improving the frequency localization of a continuous wavelet transform. This research focuses on using a synchrosqueezed wavelet transform (SWT) to determine the damping ratios of a vibrating system using a free-response signal. While synchrosqueezing is advantageous due to its localisation in the frequency, damping identification with the original SWT is not sufficiently accurate. Here, the synchrosqueezing was researched in detail, and it was found that an error in the frequency occurs as a result of the numerical calculation of the preliminary frequencies. If this error were to be compensated, a better damping identification would be expected. To minimize the frequency-shift error, three different strategies are investigated: the scale-dependent coefficient method, the shifted-coefficient method and the autocorrelated-frequency method. Furthermore, to improve the SWT, two synchrosqueezing criteria are introduced: the average SWT and the proportional SWT. Finally, the proposed modifications are tested against close modes and the noise in the signals. It was numerically and experimentally confirmed that the SWT with the proportional criterion offers better frequency localization and performs better than the continuous wavelet transform when tested against noisy signals. Abstract : Graphical abstract: Abstract : Highlights: Synchrosqueezed wavelet transform with the corrected frequency shift. Synchrosqueezing is enhanced by modifying the squeezing criterion. Enhanced Synchrosqueezed wavelet transform results in better damp-ing identification.